153k views
4 votes
B) 23 − 32 − 8 + 12 = 0Solve each equation using by factoring or using formulas

User Kochez
by
5.6k points

1 Answer

1 vote

In this case, we'll have to carry out several steps to find the solution.

Step 01:

data:

2x³ - 3x² - 8x + 12 = 0

Step 02:

solve for x:

2x³ - 3x² - 8x + 12 = 0


\begin{gathered} 2x^3-3x^2-8x+12=0 \\ \\ \left(2x-3\right)\left(x+2\right)\left(x-2\right)=0 \end{gathered}

2x - 3 = 0

x = 3/2

x + 2 = 0

x = - 2

x - 2 = 0

x = 2

The answer is:

x = 3/2

x = - 2

x = 2

User Thelandog
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.